Fungsi Pelabuhan Panjang Sebagai Pelabuhan Pengekspor Lada, 1923-1930 - Arifin; Susilowati, Endang; Rinardi, Haryono (PURBAWIDYA, 2025)
This research examines the function of Panjang Port, Lampung as a port for exporting pepper commodities in the period 1923-1930. The purpose of the study is to analyze Panjang Port as a central point in the pepper distribution route from the interior of Lampung to the international market. This study uses a historical method by collecting colonial archive sources. This study explores the relationship between colonial government policies in the development of Panjang Port and the dynamics of the pepper trade. The results of the analysis show that Panjang Port not only functions as a location for pepper shipments, but also as part of the colonial economic system that benefits the colonial party. This finding emphasizes the important function of Panjang Port in the progress of the economy and trade, especially in the Lampung region, as well as economic development in the southern Sumatra region.